A nearly complete skull of the sauropod dinosaur Diamantinasaurus matildae from the Upper Cretaceous Winton Formation of Australia and implications for the early evolution of titanosaurs - Poropat, Stephen; Mannion, P.D.; Rigby, S.L.; Duncan, R.J.; Pentland, A.H.; Bevitt, J.J.; Sloan, T.; Elliott, D.A. (2023)
Titanosaurian sauropod dinosaurs were diverse and abundant throughout the Cretaceous, with a global distribution. However, few titanosaurian taxa are represented by multiple skeletons, let alone skulls. Diamantinasaurus matildae, from the lower Upper Cretaceous Winton Formation of Queensland, Australia, was heretofore represented by three specimens, including one that preserves a braincase and several other cranial elements. Herein, we describe a fourth specimen of Diamantinasaurus matildae that preserves a more complete skull-including numerous cranial elements not previously known for this taxon-as well as a partial postcranial skeleton. The skull of Diamantinasaurus matildae shows many similarities to that of the coeval Sarmientosaurus musacchioi from Argentina (e.g. quadratojugal with posterior tongue-like process; braincase with more than one ossified exit for cranial nerve V; compressed-cone-chisel-like teeth), providing further support for the inclusion of both taxa within the clade Diamantinasauria. The replacement teeth within the premaxilla of the new specimen are morphologically congruent with teeth previously attributed to Diamantinasaurus matildae, and Diamantinasauria more broadly, corroborating those referrals. Plesiomorphic characters of the new specimen include a sacrum comprising five vertebrae (also newly demonstrated in the holotype of Diamantinasaurus matildae), rather than the six or more that typify other titanosaurs. However, we demonstrate that there have been a number of independent acquisitions of a six-vertebrae sacrum among Somphospondyli and/or that there have been numerous reversals to a five-vertebrae sacrum, suggesting that sacral count is relatively plastic. Other newly identified plesiomorphic features include: the overall skull shape, which is more similar to brachiosaurids than 'derived' titanosaurs; anterior caudal centra that are amphicoelous, rather than procoelous; and a pedal phalangeal formula estimated as 2-2-3-2-0. These features are consistent with either an early-branching position within Titanosauria, or a position just outside the titanosaurian radiation, for Diamantinasauria, as indicated by alternative character weighting approaches applied in our phylogenetic analyses, and help to shed light on the early assembly of titanosaurian anatomy that has until now been obscured by a poor fossil record.